New measurement approaches to identifying spatial concentrations of poor and low-income households in German city regions - Fina, Stefan; Schmitz, Julian; Weck, Sabine; Pfaffenbach, Carmella; Dobusch, Diane (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
The question of whether 21st-century urbanization dynamics are leading to a suburbanization of poverty in Western city regions has been on the agenda of spatial researchers and housing policymakers for over a decade now. Persistent reurbanization trends are putting increased pressure on inner-city housing markets, resulting in affordability problems for low-income households. Evidence from the US and the UK shows that financing mechanisms in the real estate sector were severely disrupted in the aftermath of the financial crisis in 2009 and subsequent years, with many households losing their homes and being forced to move. Though social security systems and social housing policies generally have a moderating effect, they vary widely across Western countries. Against this background, this paper presents three spatial observation methods tailored to the spatial analysis of poverty concentrations in Germany. The methods are based on three popular conceptualizations of poverty: material poverty, relative poverty, and the concept of neighbourhood deprivation. The main novelty presented in this paper is a cold-spot analysis of purchasing power in 33 city regions using interactive map visualizations and complemented by socioeconomic indicators. Expert feedback verifies the validity of the approach which addresses a ‘blind spot’ in assessing poverty in Germany, where many low-income households are increasingly exposed to risks of poverty despite not qualifying for social benefits.